Understanding drugs in treatment by description logics - Le Thi Bao Ngoc (Journal of Technical Education Science, 2020)
Knowledge of drugs is an essential issue that directly affects the treatment process for patients. This influence can range from combining drugs to choosing drugs that correspond to the physical state specific to a particular disease. When the number of drugs is quite large, it is difficult to gain knowledge about them. Therefore, information about drugs should be presented properly to be able to extract knowledge quickly and effectively. By the capability of knowledge representation and reasoning, description logics (DLs) can be used to represent knowledge about drugs. This article focuses on building a knowledge base about drugs by DLs. We also construct a drug ontology on Protégé with drug knowledge from relevant documents to test. Through the inferring service, the drug ontology can help users find out drugs quickly in treatment based on the basic knowledge built, (and) support to access the information of drugs.